The Influence Of Mental Health On The Achievement Of Tiger Ball Volleyball Athletes In East Bekasi District - Mochamad Qesha Arief; Jibril Gibran; Riqza Fadliansyah; Muhammad Arief Setiawan (UNIVERSITAS NEGERI MAKASSAR, 2024)
The performance of athletes is not solely influenced by physical abilities but also by mental health, which plays a significant role in achieving optimal athletic performance. This research aimed to examine the impact of mental health on the performance of volleyball athletes at the Tiger Ball Club in East Bekasi District. Using a quantitative approach with a correlational method, data were collected through two questionnaires: one measuring mental health (including anxiety, stress, and depression) and the other evaluating athletic performance based on achievements in competitions. A total of 20 male athletes participated in the study. The results revealed that the athletes exhibited moderate levels of anxiety and stress, which negatively impacted their performance. While depression was less prevalent, it still contributed to a decrease in motivation. On the other hand, athletes who reported higher levels of mental well-being were more likely to achieve better results in competitions. The findings suggest that mental health significantly affects athletic performance, with anxiety, stress, and depression serving as key factors. The study recommends that mental health support, stress management programs, and recognition of individual achievements be implemented to enhance the athletes’ performance and overall well-being.